Building an Investment Tax Incentives database Methodology and initial findings for 36 developing countries - Celani, Alessandra (OECD Publishing, 2022)
The OECD has constructed an Investment Tax Incentives database which compiles granular details on corporate income tax (CIT) incentives for investment. This paper presents the methodology used to develop the database and insights from an initial data collection in 36 developing countries. The paper describes a classification to structure quantitative and qualitative information on investment tax incentives across three dimensions: design features, eligibility conditions and their legal basis. The data reveal that tax exemptions are the most widely used CIT instrument across the 36 countries and identifies notable differences between the incentives used within and outside of Special Economic Zones (SEZs). In 80% of countries covered, at least one tax incentive supports an area related to the Sustainable Development Goals
Keywords: Finance and Investment